The coordination of sulfur in synthetic and biogenic Mg calcites: The red coral case. (15th January 2017) - Perrin, J.; Rivard, C.; Vielzeuf, D.; Laporte, D.; Fonquernie, C.; Ricolleau, A.; Cotte, M.; Floquet, N.
Abstract: Sulfur has been recognized in biogenic calcites for a long time. However, its structural position is matter of debate. For some authors, sulfur is a marker of the organic matrix while it is part of the calcite structure itself for others. To better understand the place of sulfur in calcite, sulfated magnesian calcites (S-MgCalcite) have been synthetized at high pressure and temperature and studied by μ-XANES spectroscopy. S-MgCalcite XANES spectra show two different types of sulfur: sulfate (SO4 2− ) as a predominant species and a small contribution of sulfite (SO3 2− ), both substituting for carbonate ions in the calcite structure. To address the question of the position of sulfur in biogenic calcites, the oxidation states of sulfur in the skeleton and organic tissues of Corallium rubrum have been investigated by micro X-ray fluorescence (μ-XRF) and sulfur K-edge micro X-ray absorption near edge structure (μ-XANES) spectroscopy at the European Synchrotron Radiation Facility (ESRF, Grenoble, France) on beamline ID21. In the skeleton, sulfur is mainly present as oxidized sulfur SO4 2− (+VI), plus a weak sulfite contribution. XANES spectra indicate that sulfur is inorganically incorporated as sulfur structurally substituted to carbonate ions (SSS). Although an organic matrix is present in the red coral skeleton, reduced organic sulfur could not be detected by μ-XANES spectroscopy in the skeleton probably due to low organic/inorganic sulfur ratio. In the organic tissues surrounding the skeleton, several sulfur oxidation states have been detected including disulfide (S–S), thioether (R–S–CH3 ), sulfoxide (SO2 ), sulfonate (SO2 O − ) and sulfate (SO4 2− ). The unexpected occurrence of inorganic sulfate within the organic tissues suggests the presence of pre-organized organic/inorganic complexes in the circulatory system of the red coral, precursors to biomineralization ahead of the growth front.